Southwest Gardens: Matching Plants with Available Water Resources - Goldenetz, Jolie A. (Arizona-Nevada Academy of Science, 2007)
From the Proceedings of the 2007 Meetings of the Hydrology Section - Arizona-Nevada Academy of Science - March 31, 2007, Nothern Arizona University, Flagstaff, Arizona